Warming increases the number of apparent prey in reaction field volume of zooplanktivorous fish. (5th October 2017) - Gliwicz, Z. Maciej; Babkiewicz, Ewa; Kumar, Rajeev; Kunjiappan, Selvaraj; Leniowski, Konrad
Abstract: Improved vision due to the cranial endothermy known in large‐bodied marine fishes suggests that increased water temperature alone might also increase the speed with which visual information can be processed and therefore improve the vision of small planktivorous fish without invoking endothermic heating. We check this for two freshwater species by testing whether a temperature increase results in an increase in the reaction distance (RD), the distance from which a foraging fish can spot its tiny zooplankton prey. We demonstrate that at a given light intensity, with a temperature increase of 10°C, both the reaction field volume and prey encounter rate of planktivorous fish are doubled due to a 21–23% increase in RD. This was found for each of the two small‐bodied freshwater planktivorous fishes: rudd from the temperate zone (foraging at 16°C and 26°C), and Malabar danio from the tropics (foraging at 21°C and 31°C), and may be expected to be important for other fishes as well. An increase in RD at a higher temperature could translate into a higher "apparent prey density" or number of prey within the reaction field volume of a foraging fish (a vertically flattened hemisphere or cone with a horizontal radius equal to the RD). For fish in the wild, this information may compel them to continue foraging despite a low actual density of prey in the habitat. This is particularly important while feeding under the risk of predation, when attention is partially allocated to risk assessment.